Clarification on the circumscription of Prescottia glazioviana (Cranichidinae, Orchidaceae) - de Azevedo, Cecília O.; Leoni, Lúcio De Souza; van Den Berg, Cássio (Phytotaxa, 2012)
Prescottia glazioviana is a rare and poorly known species, for which this paper clarifies the circumscription, indicating for the first time diagnostic morphological features that were missing in the original description. An amended description, distribution data and a detailed illustration are presented. Previously known from only two collections from Rio de Janeiro State, P. glazioviana is reported for the first time in Minas Gerais State, Brazil.